2014
DOI: 10.1021/la503228v
|View full text |Cite
|
Sign up to set email alerts
|

Sub-10 nm Monoclinic Gd2O3:Eu3+ Nanoparticles as Dual-Modal Nanoprobes for Magnetic Resonance and Fluorescence Imaging

Abstract: Monoclinic Gd2O3:Eu(3+) nanoparticles (NPs) possess favorable magnetic and optical properties for biomedical application. However, how to obtain small enough NPs still remains a challenge. Here we combined the standard solid-state reaction with the laser ablation in liquids (LAL) technique to fabricate sub-10 nm monoclinic Gd2O3:Eu(3+) NPs and explained their formation mechanism. The obtained Gd2O3:Eu(3+) NPs exhibit bright red fluorescence emission and can be successfully used as fluorescence probe for cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 56 publications
(116 reference statements)
0
51
0
Order By: Relevance
“…Various studies have demonstrated that nano materials, like Gd2O3, can be used as highly sensitive CAs [6][7][8]. Gd2O3 based NPs have a high density of paramagnetic gadolinium ions in a small volume and enhanced surface to volume ratio which results in a high relaxivity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated that nano materials, like Gd2O3, can be used as highly sensitive CAs [6][7][8]. Gd2O3 based NPs have a high density of paramagnetic gadolinium ions in a small volume and enhanced surface to volume ratio which results in a high relaxivity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…32 Our recent work has focused on the synthesis and development of ultra-small (sub-10 nm) lanthanide-doped Gd 2 O 3 nanoparticles for MR/fluorescence dual-modal imaging. [33][34][35][36] However, to the best of our knowledge, the ability of lanthanide-doped Gd 2 O 3 UCNs for theranostics application, which combines the diagnosis and treatment of cancer, has not previously been reported. In this contribution, the aim was to synthesis magnetic and fluorescent lanthanide-doped Gd 2 O 3 UCNs and simultaneously achieve MR/UCL dual-modal imaging and PDT.…”
Section: Liu Et Almentioning
confidence: 99%
“…This coexistence of properties can be used for imaging techniques such as multimodal SERS-MRI-CT [62]. It is also possible to combine magnetic resonance and fluorescence properties for dual-modal imaging agents [79,80]. For this purpose, Gd 2 O 3 , the magnetic resonance imaging contrast agent, can be doped with Eu 3+ [79] or Tb 3+ [80] as a fluorescence-emitting center.…”
Section: Dual Functionsmentioning
confidence: 99%
“…It is also possible to combine magnetic resonance and fluorescence properties for dual-modal imaging agents [79,80]. For this purpose, Gd 2 O 3 , the magnetic resonance imaging contrast agent, can be doped with Eu 3+ [79] or Tb 3+ [80] as a fluorescence-emitting center. Doping is easily carried out by mixing both oxide powders, their milling, target pressing, and sintering [79].…”
Section: Dual Functionsmentioning
confidence: 99%